(untitled) (American Journal of Interdisciplinary Research and Development, 2022)
The study examined the physical-chemical, mechanical and structural properties of the local raw material - reed plant and fiber waste from cotton ginning, textile and other industries, the cellular cellulose obtained on the basis of the map.